Effects of recycled sand and nanomaterials on ultra-high performance concrete: Workability, compressive strength and microstructure. (16th May 2023) - Feng, Yuan; Zhang, Baifa; Xie, Jianhe; Xue, Zixin; Huang, Kunhong; Tan, Jiakun
Highlights: Effects of combined usage of recycled sand and nanomaterials on the properties of UHPC is investigated. The enhancement mechanism of recycled sand UHPC by different nanomaterials is revealed. An economic and effective approach to optimize the performance of recycled sand UHPC is presented. Abstract: The use of recycled sand (RS) from construction and demolition (C&D) waste to produce ultra-high performance concrete (UHPC) is a promising but challenging methodology for low-carbon technology innovation. In this study, an economic and effective approach to optimize the performance of recycled sand UHPC (RSUHPC) is developed. An experimental study was conducted to investigate the effects of RS and nanomaterials on the physical properties, mechanical behaivour, and microstructure of UHPC. The results show that the compressive performance of RSUHPC decreased with increasing RS content, but the addition of nanomaterials can significantly counteract this negative impact. Nanomaterial incorporation in the mix had an impact on the fresh and hardened properties and the microstructure of the reaction products. Based on the synthetic consideration of the performance improvement and economic cost, a content of 25% RS and 1% NS is optimal for RSUHPC. After modification with 1% NS, the compressive strength of RSUHPC at 28 days increased by 14%, reaching 152 MPa.